I'm betting you meant 6x-3y=15.
I'm going to factor this.
3(2x-y)=15
3(2x-y)/3=15/3
2x-y=5
Let's assume y=-1, shall we?
2x-(-1)=5
2x+1=5
2x+1-1=5-1
2x=4
2x/2=4/2
x=2
Let's plug them into the original equation, shall we?
6(2)-3(-1)=15
12-(-3)=15
12+3=15
15=15
It's true.
-6x^2 - 78x - 252 Improved answer: -6x+6x+7 When simplified = 7
There is no possible value of 'x' for which (6x-2) can be equal to (6x-12).
-6x-4-8 = -6x -12
There is no simplification. It is sqrt(6X +4)There is no simplification. It is sqrt(6X +4)There is no simplification. It is sqrt(6X +4)There is no simplification. It is sqrt(6X +4)
That depends on what you mean by "6x 5", which could be 6x * 5, 6x + 5, 6x - 5, 6x / 5, 6x5, etc.
The GCF is 6x.
-2
-6x^2 - 78x - 252 Improved answer: -6x+6x+7 When simplified = 7
1+6x+6x+8 1+ 12x +8 12x + 9 = 21 + x
6x - 9 = 21 6x = 21 + 9 6x = 28 x = 28/6 Reduce to: x = 14/3
There is no possible value of 'x' for which (6x-2) can be equal to (6x-12).
-6x = 2y - 120 -2y -2y -2y - 6x = -120 +6x +6x -2y = 6x - 120 -2y/-2 = 6x/-2 - 120/-2 y = -3x + 60
d2 [6x]d3[6x]d2[6x]d1[6x]d2[6x]d3[6x]d2[3x]d1[3x]d0[3x]
d/dx (ln(6x)) = (d/dx (6x))/(6x) = 6/6x = 1/x
-6x-4-8 = -6x -12
There is no simplification. It is sqrt(6X +4)There is no simplification. It is sqrt(6X +4)There is no simplification. It is sqrt(6X +4)There is no simplification. It is sqrt(6X +4)
That depends on what you mean by "6x 5", which could be 6x * 5, 6x + 5, 6x - 5, 6x / 5, 6x5, etc.